MODEL KOMUNIKASI PADA PROSES PEMBELAJARAN DALAM JARINGAN Learning Management System (LMS) KELAS X TEKNIK KOMPUTER DAN JARINGAN SMK TELKOM MAKASSAR - Andi Sri Wahdaniar; Amaluddin Amaluddin; Abd Majid (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2020)
This thesis discusse Government Public relations strategy in optimizing Media relations for government activities in Pinrang regency, The purpose of the research : (1) To Know The media relations strategy of Pinrang Regency Public Relations. (2) To Know what are the obstacles faced by Pinrang Regency Public Relations in optimizing media relations in governmental activities. This research lasted for one month and located in Pinrang. Then, the informants in this research were 2 People each of them has the task and responsibility of disseminating information on activities in governance in Pinrang district. The research method is a qualitative research method. Data collection techniques are observation and interviews. The results of this research shows that with the development of the era of Public Relations, the Pinrang Regency Government utilizes Media Relations such as online media etc as a bridge for public information to optimize government activities in Pinrang regency. In the process of establishing a Media Relations there are several obstacles that are faced, however, these are continuously studied in order to continue to improve the quality of Public Relations in carrying out its main duties.